Imobilisasi kulit Lengkeng (euphoria longan lour) terhadap penyerapan ion logam Kadmium - Cillia Marfania (CHEMPUBLISH JOURNAL, 2019)
The use of longan skin biosorbents has been shown to reduce environmental pollution caused by heavy metals. Because it has an active site and its facial pores can support the absorption process, it is inexpensive and environmentally friendly. However, the ability of longan skin in absorption has several limitations such as particles that are lightweight, easily damaged and of low specific gravity. To overcome this, various methods have been carried out, one of which is the immobilization of sodium silica. The biosorption method used was the bath method. The results of this study, optimum absorption of Cd metal ions occurred at a concentration of 250 ppm, with a contact time of 120 minutes and a speed of 250 rpm.